PELATIHAN KETERAMPILAN MENDESAIN KEMASAN DAN BRANDING DALAM PENJUALAN PRODUK (BERAS SETRA RAMOS) DI WILAYAH CIAWI KABUPATEN TASIKMALAYA - depy muhamad pauzy; Dudu Risana (Politeknik Negeri Sriwijaya, 2021)
The purpose of this Community Service program through the Application of Appropriate Technology (PTTG) is to assist producers (Setra Ramos Rice) in developing their businesses so that they are more advanced and increase their businesses, so that they can improve their standard of living and prosper. The method taken by the team in improving the welfare of the partners begins with an analysis of the situation in the field to find out the problems faced by the partners. The method used in the Application of Appropriate Technology (PTTG) is to provide theory and carry out direct activities in the form of practice. In order to support the realization of the methods offered by the service team, the PTTG work procedure includes the location survey stage, the preparation/activity plan stage, the socialization stage, the activity implementation stage, the evaluation stage, and the report generation stage. The results of the implementation of service to these partners are: 1) An increase in the knowledge of business actors (Beras Setra Ramos) about the importance of product attribute quality 2) an increase in developing soft skills in designing packaging and product branding 3) an increase in knowledge of product business actors (Beras Setra Ramos) in the Application of Marketing Technology. Keywords : Packaging Design, Branding, Setra Ramos Rice, PKM